Increasing the precision of measurement of postures in free space - Towle, Josie A. (1986)
The project set out to use a very precise three dimensional tracking system to identify changes in joint condition for use in clinical assessment. Untried and untested the CODA-3 was brought into the department and put through a six month period of validification in order to evaluate it's capabilities. These are described in detail in the text. Once satisfied that the equipment was capable of measuring minute rapidly changing position of it's prismatic markers, pilot studies were devised to assess it's ability to reproduce the results from well recognised gait-analysis techniques. It gave promising results.